Morphometric Assessment of Occipital Condyles and Foramen Magnum Reveals Enhanced Sexual Dimorphism Detection via 3D Imaging: A Systematic Review and Meta-Analysis Utilizing Classification and Regression Trees - Tsiouris, Christos; Triantafyllou, George; Karangeli, Nektaria; Botis, George G.; Papadopoulos-Manolarakis, Panagiotis; Kalamatianos, Theodosis; Tsakotos, George; Piagkou, Maria (Diagnostics (Basel), 2025)
Background: The morphology of the occipital condyles (OCs) and foramen magnum (FM) is critical for neurosurgical planning and forensic identification. However, pooled reference values and the impact of study-level moderators on morphometric estimates remain underexplored. Methods: A systematic review and meta-analysis were conducted to estimate pooled morphometric values of the OCs and FM. Databases were searched for studies reporting relevant data in adult human subjects. A random-effects model was used to calculate pooled means and mean differences (MDs) by sex and side (left vs. right). Risk of bias and study quality were assessed. Subgroup analyses were conducted based on study design (osteological vs. imaging) and geographical region. Meta-CART (classification and regression trees) was used to explore moderator interactions and identify data-driven subgroups contributing to heterogeneity. Results: A total of 61 studies comprising 8010 adult skulls met the inclusion criteria. Substantial heterogeneity was observed across studies; most were assessed as having low-to-moderate methodological quality and a high risk of bias. The pooled mean values were as follows: OC length (OCL): 21.51 mm, OC width (OCW): 11.23 mm, OC thickness (OCT): 9.11 mm, FM length (FML): 35.02 mm, and FM width (FMW): 28.94 mm. Morphometric values reported in imaging-based studies were consistently lower than those from osteological studies. Evident sexual dimorphism was identified, with males exhibiting larger dimensions than females. The most pronounced sex-based mean differences (MDs)—approximately 2 mm—were found in OCL, FML, and FMW. In contrast, differences in OCT and OCW were under 1 mm. No significant side-related asymmetries were observed overall. Subgroup analysis revealed that sex-related MDs were more prominent in imaging studies, particularly for the right OCL and OCW. Meta-CART analysis identified study design as the strongest moderator for OCL, OCW, and FML. Sexual dimorphism was more pronounced in imaging studies but statistically insignificant in osteological samples. Furthermore, sex emerged as a stronger predictor for OCL than OCW, while geographical region had a greater impact on OCW. For OCT, geographical region was the main influencing factor, whereas sex was the primary moderator for FMW. Conclusions: OC and FM morphometry exhibit substantial heterogeneity across studies. Imaging-based methods more effectively detect sex-related differences, underscoring their utility in forensic identification and neurosurgical planning. These findings emphasize the need for more standardized, high-quality morphometric research to support population-specific anatomical reference data.